Factors influencing the underutilization of mental health services among Asian American women with a history of depression and suicide - Augsberger, Astraea (BMC Health Serv Res, 2015)
BACKGROUND: Despite the substantially high prevalence of depression, suicidal ideation and suicide attempts among Asian American women who are children of immigrants, little is known about the prevalence of mental health utilization and the perceived barriers to accessing care. METHODS: The data were from the Asian American Women’s Sexual Health Initiative Project (AWSHIP), a 5-year mixed methods study at Boston University. The quantitative analysis examined the differential proportion of mental health utilization among 701 survey participants based on their mental health risk profile determined by current moderate to severe depression symptoms and lifetime history of suicidality. Mental health risk groups were created based on participants’ current depression symptoms and history of suicide behaviors: Group 1–low-risk; Group 2–medium-risk; Group 3–high-risk. Mental health care utilization outcomes were measured by any mental health care, minimally adequate mental health care, and intensive mental health care. The qualitative analysis explored the perceived barriers to mental health care among 17 participants from the medium and high-risk groups. RESULTS: Among 701 participants, 43 % of women (n = 299) reported that they either suffered from current moderate to severe depression symptoms or a lifetime history of suicidal ideation or suicide attempt. Although the high-risk group demonstrated statistically significant higher mental health utilization compared to the low and medium-risk groups, more than 60 % of the high-risk group did not access any mental health care, and more than 80 % did not receive minimally adequate care. The qualitative analysis identified three underutilization factors: Asian family contributions to mental health stigma, Asian community contributions to mental health stigma, and a mismatch between cultural needs and available services. CONCLUSIONS: Despite the high prevalence of depression and suicidal behaviors among young Asian American women in the sample, the proportion of mental health care utilization was extremely low. The qualitative analysis underscores the influence of Asian family and community stigma on mental health utilization and the lack of culturally appropriate mental health interventions. Prevention and intervention efforts should focus on raising mental health awareness in the Asian American community and offering culturally sensitive services.